POTENSI ANTIMIKROBA EKSTRAK DAUN PEPAYA (Carica papaya L.) MENGGUNAKAN METODE BIOAUTOGRAFI TERHADAP BAKTERI Streptococcus sp - Tri Puji Lestari Sudarwati (Akademi Farmasi Yarsi Pontianak, 2021)
Carica papaya L is one of herbal plant that has been known as a traditional medicine of bacterial infections with various bioactivities such as an antiseptic, antiinflammatory, antifungal and antibacterial. This research aims to determine the antibacterial activity of the extracts ethanol leaf of papaya (Carica papaya L) against Streptococcus sp. Extract ethanol were obtained by maceration method and were tested using bioautography method. The extracts ethanol leaf of papaya can inhibit growth of Streptococcus sp at consentrations 2%, 4%, 6%, 8% and 10% with average inhibitory zone diameter that are 5,52 mm; 6,34 mm; 7,06 mm; 7,72 mm and 8,9 mm. TLC bioautography assay with eluen n-butanol : acetate acid : aquadest (4 : 1 : 5) is obtained inhibitory zone at stain with Rf value 0,93. Result of identification shown that the stain are tannin. Statistical result of Anova Oneway showed significant difference from each concentration.